Acute myocardial infarction preferentially alters low-abundant, long-chain unsaturated phospholipid and sphingolipid species in plasma high-density lipoprotein subpopulations - Maharajah Ponnaiah; Emile Zakiev; Marie Lhomme; Fabiana Rached; Laurent Camont; Carlos V. Serrano, Jr.; Raul D. Santos; M. John Chapman; Alexander Orekhov; Anatol Kontush (Atherosclerosis Plus, 2024)
Aim: High-density lipoprotein (HDL) particles in ST-segment elevation myocardial infarction (STEMI) are deficient in their anti-atherogenic function. Molecular determinants of such deficiency remain obscure. Methods: Five major HDL subpopulations were isolated using density-gradient ultracentrifugation from STEMI patients (n = 12) and healthy age- and sex-matched controls (n = 12), and 160 species of phosphatidylcholine, lysophosphatidylcholine, phosphatidylethanolamine, phosphatidylinositol, phosphatidylglycerol, phosphatidylserine, phosphatidic acid, sphingomyelin and ceramide were quantified by LC-MS/MS. Results: Multiple minor species of proinflammatory phosphatidic acid and lysophosphatidylcholine were enriched by 1.7–27.2-fold throughout the majority of HDL subpopulations in STEMI. In contrast, minor phosphatidylcholine, phosphatidylglycerol, phosphatidylinositol, phosphatidylethanolamine, sphingomyelin and ceramide species were typically depleted up to 3-fold in STEMI vs. control HDLs, while abundances of their major species did not differ between the groups. Intermediate-to-long-chain phosphatidylcholine, phosphatidylinositol and phosphatidylglycerol species were more affected by STEMI than their short-chain counterparts, resulting in positive correlations between their fold decrease and the carbon chain length. Additionally, fold decreases in the abundances of multiple lipid species were positively correlated with the double bond number in their carbon chains. Finally, abundances of several phospholipid and ceramide species were positively correlated with cholesterol efflux capacity and antioxidative activity of HDL subpopulations, both reduced in STEMI vs controls. KEGG pathway analysis tied these species to altered glycerophospholipid and linoleic acid metabolism. Conclusions: Minor unsaturated intermediate-to-long-chain phospholipid and sphingolipid species in HDL subpopulations are most affected by STEMI, reflecting alterations in glycerophospholipid and linoleic acid metabolism with the accumulation of proinflammatory lysolipids and maintenance of homeostasis of major phospholipid species.